GETAK MASK DANCE IN PAMEKASAN MADURA AS A MANIFESTATION OF PRABU BALADEWA FIGURE - Rahayu, Eko Wahyuni (Sembadra, Journal of Arts and Education Studies, 2021)
Getak mask dance is one of traditional dances from Pamekasan, Madura. This dance depicts the bravery of a knight who is wandering and has a patriot spirit. This article aims to identify and record the existence of Getak Mask Dance both textually and contextually. It is because the existence of this dance has started to fade. Therefore, it is necessary to immediately record as an effort to preserve. Historically, the existence of Getak Mask Dance is closely related to the performance of œdramatari topeng dhalang Madura which is based on Mahabharata story. It is then developed to a part of Ludruk Sandur performance. Gethak Mask Dance is a manifestation of Balarama figure; a king in Madura Kingdom. Balarama is a character in wayang performance who is highly respected by Madurese people and considered as their ancestor. Textually, the choreography of Getak Mask Dance is in the form of a male single dance, he uses white mask and has a strong character. The dance movement pattern is very distinctive, supported by the sound of Kendang or drum which sounds œGe and œTak and the use of handkerchief property as a symbol of weapon. Keywords: Getak Mask Dance, Pamekasan, manifestation, Baladewa figure